2016
DOI: 10.3389/fpsyt.2016.00127
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Caregivers of ADHD Children and Diabetes Patients

Abstract: introduction: Studies have shown that the presence of attention-deficit hyperactivity disorder (ADHD) causes great impairment in academic, social, and professional activities as well as in the quality of life (QoL) of its patients. Similarly, the impact caused by other chronic disorders, such as diabetes, in the patient's QoL has been emphasized in many studies. Despite its relevance, no study has yet investigated whether ADHD caregivers and diabetic patients would have similar QoL impairment.Objectives: This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 46 publications
3
11
0
7
Order By: Relevance
“…On the basis of results from other studies involving parents with chronically ill children, we found similar results were obtained from the parents of children with congenital metabolic disorders [22]. WHS carers presented a lower QoL than other studies of children with epilepsy, attention de cit hyperactivity disorder and cerebral palsy [84,85]. We have found negative associations between QoL and caregiver's strain, such us, depression and burnout, nevertheless, resources such as engagement strategies appeared to improve QoL domains.…”
Section: Caregivers' Psychosocial and Clinical Statussupporting
confidence: 81%
“…On the basis of results from other studies involving parents with chronically ill children, we found similar results were obtained from the parents of children with congenital metabolic disorders [22]. WHS carers presented a lower QoL than other studies of children with epilepsy, attention de cit hyperactivity disorder and cerebral palsy [84,85]. We have found negative associations between QoL and caregiver's strain, such us, depression and burnout, nevertheless, resources such as engagement strategies appeared to improve QoL domains.…”
Section: Caregivers' Psychosocial and Clinical Statussupporting
confidence: 81%
“…On the basis of results from other studies involving parents with chronically ill children, we found similar results were obtained from the parents of children with congenital metabolic disorders [22]. WHS carers presented a lower QoL than other studies of children with epilepsy, attention deficit hyperactivity disorder and cerebral palsy [84,85].…”
Section: Caregivers' Psychosocial and Clinical Statussupporting
confidence: 80%
“…On the basis of results from other studies involving parents with chronically ill children, we found similar results were obtained from the parents of children with congenital metabolic disorders [21]. WHS carers presented a lower QoL than other studies of children with epilepsy, attention deficit hyperactivity disorder and cerebral palsy [86,87].…”
Section: Caregivers' Psychosocial and Clinical Statussupporting
confidence: 80%